2005
DOI: 10.1637/7246-072904r
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Changes of the Fusion Protein Gene of Chicken Embryo Fibroblast–Adapted Velogenic Newcastle Disease Virus: Effect on Its Pathogenicity

Abstract: Molecular changes of cell culture-adapted Newcastle disease virus (NDV) were studied by adapting a velogenic NDV isolated from commercial layer chicken-to-chicken embryo fibroblast (CEF) cells. The isolate was passaged 50 times in CEF cells. At every 10th passage the virus was characterized conventionally by mean death time analysis, intracerebral pathogenicity index, and virus titration. As the passage level increased, a gradual reduction in the virulence of the virus was observed. Molecular characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The failure of virus isolation from the blood samples at day 3 post-infection might be due to the lodgment of the virus in different tissues of the infected birds at day 3 of post infection. The findings of NDV isolation using CEF cell culture system has close agreement with the findings of Mohan et al (2005) and Takehara et al (1987). In their study, the isolation rate of NDV was higher in CEF culture system compared to that of avian embryo.…”
Section: Isolation Of Ndvsupporting
confidence: 79%
“…The failure of virus isolation from the blood samples at day 3 post-infection might be due to the lodgment of the virus in different tissues of the infected birds at day 3 of post infection. The findings of NDV isolation using CEF cell culture system has close agreement with the findings of Mohan et al (2005) and Takehara et al (1987). In their study, the isolation rate of NDV was higher in CEF culture system compared to that of avian embryo.…”
Section: Isolation Of Ndvsupporting
confidence: 79%
“…(Table 2), and is identical to the motif found in the virulent isolates from Indonesia, Vietnam, Taiwan, Germany and U.S.A. [7,23]. Changes in the F protein cleavage site motif have been shown to alter the virulence of NDVs and changing virulent clones to avirulent ones [14] and vice versa [6,24,27]. In particular, the LaSota strain, which is used as a vaccine in Indonesia, was shown to acquire virulence by a change in the F cleavage site motif [6,27].…”
Section: Discussionmentioning
confidence: 60%
“…When compared to the AHFV NC004355 and AHFV JF 416949 strains, a total of 139-203 nucleotides were missing from the AHFV/997/NJ/09/SA strain primarily in the UTR, likely due to passage of the virus in cell culture. Previous studies reported such deletions and even insertions and/or duplications of nucleotides of viruses when passaged in cultures [16,17,18,19,20,21]. Several studies have shown that nucleotide deletion/insertion/duplication occur in the 3′ UTR (formerly known as a noncoding region or NCR) among various members of flaviviruses and even among strains of the same viral species [16,17], as well as in the 5′ UTR of hepatitis A virus [18] and the Newcastle disease virus genome [19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported such deletions and even insertions and/or duplications of nucleotides of viruses when passaged in cultures [16,17,18,19,20,21]. Several studies have shown that nucleotide deletion/insertion/duplication occur in the 3′ UTR (formerly known as a noncoding region or NCR) among various members of flaviviruses and even among strains of the same viral species [16,17], as well as in the 5′ UTR of hepatitis A virus [18] and the Newcastle disease virus genome [19]. In another study it was observed that size variation between yellow fever virus strains was due to duplications and/or deletions of repeated nucleotide sequence elements that occurred in the 3′ UTR by passaging the virus in cell culture [20].…”
Section: Discussionmentioning
confidence: 99%